Reconciling the global public health interest with intellectual property protection through the waiver of certain provisions of the WTO TRIPS Agreement - Makore, Shelton T Mota; Osode, Patrick; Lubisi, Nombulelo (Yuridika, 2022)
The rapid spread of the SARS-CoV-2 virus which is responsible for the COVID-19 pandemic across the globe has spawned an intense debate on the necessity of a waiver of some provisions of the World Trade Organisation's Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) to increase access to medicines and other medical technologies essential for combating the disease. This article explores the potential of the TRIPS waiver as a mechanism for reconciling the conflicting norms of public health with intellectual property rights protection. It argues that while the TRIPS waiver can be an effective legal instrument which accommodates public health concerns of increasing access to medicines and medical technologies, it has, in its current form and text, many flaws which militate against its effectiveness. These flaws are evident in the way the TRIPS waiver is couched, notwithstanding that the waiver presents multiple benefits including furthering re-humaninisation, distributive justice and decolonisation goals. The article offers recommendations on how the TRIPS waiver adopted during the WTO's recently concluded 12th Ministerial Conference could be strengthened to eliminate some of its defects in pursuit of expanding access to COVID-19 vaccines and other therapeutic. The research methodology used in this article is the qualitative desktop doctrinal research methodological approach.